Two Novel E-Visas Verification Schemes Based On Public Key Infrastructure (Pki) And Identity Based Encryption (Ibe). - Abuadhmah, Najlaa Abdullah (2010)

(untitled)
Visa merupakan dokumen perjalanan yang sangat penting yang membenarkan kita memasuki sesebuah negara yang akan kita lawati.